2020
DOI: 10.1002/slct.202001529
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Synthesis of a Sulfur‐Polyacrylonitrile Composite Cathode for Lithium‐Sulfur Batteries

Abstract: Through a novel synthesis process, a novel sulfurized polyacrylonitrile (SPAN) composite, noted as DH-150-300-SPAN, was prepared and tested as cathode material for lithium sulfur (LiÀ S) batteries. The reported process involves two heating steps at low temperature. The first plateau at 150°C melts elemental sulfur, while the second, at 300°C, produces the cycling of polyacrylonitrile, and incorporates sulfur to the cyclic polymeric structure. A fully morphological and electrochemical characterization was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…However, the SPAN suffers from unsatisfactory Coulombic efficiency (CE, defined as Q charge / Q discharge ) on the first cycle, and there is still space for further improvement of the rate capability . In a review of previous reports that have provided CE information, the SPAN materials that cycled in carbonate electrolytes have also shown problems. , An initial CE value <75% was generally presented irrespective of the morphology of the SPAN. , For instance, the powdery SPAN material reported by Wang et al exhibited an initial CE of 62% at 50 mA g –1 . That reported by Jerez et al showed an initial CE of 64.7% at a current rate of 0.1 C (1 C = 1675 mA g –1 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the SPAN suffers from unsatisfactory Coulombic efficiency (CE, defined as Q charge / Q discharge ) on the first cycle, and there is still space for further improvement of the rate capability . In a review of previous reports that have provided CE information, the SPAN materials that cycled in carbonate electrolytes have also shown problems. , An initial CE value <75% was generally presented irrespective of the morphology of the SPAN. , For instance, the powdery SPAN material reported by Wang et al exhibited an initial CE of 62% at 50 mA g –1 . That reported by Jerez et al showed an initial CE of 64.7% at a current rate of 0.1 C (1 C = 1675 mA g –1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In a review of previous reports that have provided CE information, the SPAN materials that cycled in carbonate electrolytes have also shown problems. , An initial CE value <75% was generally presented irrespective of the morphology of the SPAN. , For instance, the powdery SPAN material reported by Wang et al exhibited an initial CE of 62% at 50 mA g –1 . That reported by Jerez et al showed an initial CE of 64.7% at a current rate of 0.1 C (1 C = 1675 mA g –1 ) . Some fibrous SPAN materials are no exception. Ye et al reported SPAN nanofibers with an initial CE of 56.9% at 200 mA g –1 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the micrometric features of the composite can lower the impact of the side processes associated with the electrolyte decomposition on the overall reversibility of the main electrochemical reaction, and the high amount of the sulfur may ensure a high practical capacity and scalability of the composite material. 63 The S:MWCNTs 90:10 w/w composite is subsequently included in a cathode and cycled in a lithium cell using the DOL:DME-control electrolyte, as reported in Figure 4. The voltage profiles of the rate capability test displayed in Figure 4a,b show the typical signature of the Li−S conversion process, where two galvanostatic discharge plateaus at 2.3 and 2.1 V are reflected during subsequent charge in merging steps at 2.3 and 2.4 V. 64−66 The discharge plateau at the higher voltage (i.e., 2.3 V) actually accounts for the initial conversion of Li and S to long chain polysulfides such as Li 2 S 8 , instead the one at the lower voltage (∼2.1 V) reflects the complex equilibrium including intermediate radical species during which the polysulfides are shortened to form Li 2 S 4 , Li 2 S 2 , and possibly Li 2 S by subsequent reductions.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of additional signals accounting for undesired species excludes byproducts possibly formed during material synthesis which can lead to side reactivity during the Li–S conversion process, and confirms the suitability of the sulfur–carbon melt-mix process conducted at mild temperature. The success of the sulfur composite preparation is further confirmed by TGA and the corresponding DTG in Figure b, which reveals a sole weight loss between 200 and 380 °C accounting for the sulfur evaporation with a ratio of 90% of the total mass, exactly corresponding to the predicted amount . The SEM images acquired in secondary electron mode in Figure c,d show large sulfur clusters ranging from 10 to 100 μm (Figure c) formed by submicrometric primary particles covered by a thin layer of MWCNTs (Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation